Physiological responses and their associations to external load immediately and 12 hours after official ice hockey match in Finnish elite ice hockey players - Halonen, E. (Faculty of Sport and Health Sciences, University of Jyväskylä, 2020)
Introduction. Knowledge about physiological responses and sufficient recovery times after matches are needed in professional team sports to avoid illnesses, injuries and overtraining. In many team sports (e.g. soccer, rugby, handball and basketball), such knowledge has been attained, however, in ice hockey research in this area is lacking. Therefore, the aim of this study wasto identify the physiological responses and their associations to external load in official Finnish elite league ice hockey match. Methods. The study subjects were 38 Finnish elite league ice hockey players. The study was done in single group repeated measures design, where measurements were done before, during, immediately and 12 hours after thematch. The pre-and post-match measurements included venous blood samples for leukocytes, lymphocytes and creatine kinase(CK), salivary samples for testosterone (T), cortisol (C), testosterone to cortisol -ratio (T/C), DHEA-S and IgA and the assessment of neuromuscular performance by measuring jump height, maximum power, flight times, take-off times and flight time to take-off time -ratios (FT/TT) from countermovement jump (CMJ). Also, match activity data, heart ratesand session-RPE (sRPE) were recordedduring the match. Results.Maximum power, FT and FT/TT in CMJ increased at post 0h. At post 12h maximum power and FT returned to baseline, whereas FT/TT remained improved. CK increased at post 0h and further increased at post 12h. T and T/C decreased at post 0hwith no change in C, whereas DHEA-S increased. No significant differences were found in T, C, T/C or DHEA-S between baseline and post 12h values. Circulating leukocytes increased and lymphocytes decreased at post 0hwith no change in salivary IgA. At post 12 hlymphocytes returned to baseline and leukocytes remained elevated. Greater skating intensity was associated with increased T and DHEA-S at post 12h. sRPE correlated with the amount of high-intensity skating, acute changes in T, DHEA-S and IgA and with changes in C and DHEA-S between post 0h and post 12h. Conclusions. Ice hockey match does not seem to impair neuromuscular performance, but other markers indicate that the players are not fully recovered 12 hours after the match. External load is poorly associated with physiological responses to ice hockey match. Hence, more research is needed to better understand the individual responses to ice hockey matches.